2017
DOI: 10.3390/ijms18112312
|View full text |Cite
|
Sign up to set email alerts
|

Actions of Brain-Derived Neurotrophic Factor and Glucocorticoid Stress in Neurogenesis

Abstract: Altered neurogenesis is suggested to be involved in the onset of brain diseases, including mental disorders and neurodegenerative diseases. Neurotrophic factors are well known for their positive effects on the proliferation/differentiation of both embryonic and adult neural stem/progenitor cells (NSCs/NPCs). Especially, brain-derived neurotrophic factor (BDNF) has been extensively investigated because of its roles in the differentiation/maturation of NSCs/NPCs. On the other hand, recent evidence indicates a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(97 citation statements)
references
References 96 publications
4
89
0
4
Order By: Relevance
“…In stressrelated disorders depletion of serotonin reduces brain BDNF levels (Chen et al, 2007;Yoshida et al, 2012;Zhou et al, 2008). On the contrary, hypo-serotonergic mouse (Tph2-/-or Pet1-/-) showed increased BDNF levels in hippocampus and prefrontal cortex (Diaz et al, 2013;Klempin et al, 2013;Kronenberg et al, 2016;Sachs et al, 2013) and humans with serotonin transporter deficiency (hyperserotonin) reduced the availability of BDNF (Molteni et al, 2010), which enhances NSCs proliferation and neurogenesis (Arsenijevic and Weiss, 1998;Numakawa et al, 2017). Our findings support the negative role of serotonin on BDNF signaling and NSC plasticity.…”
Section: Discussionsupporting
confidence: 73%
“…In stressrelated disorders depletion of serotonin reduces brain BDNF levels (Chen et al, 2007;Yoshida et al, 2012;Zhou et al, 2008). On the contrary, hypo-serotonergic mouse (Tph2-/-or Pet1-/-) showed increased BDNF levels in hippocampus and prefrontal cortex (Diaz et al, 2013;Klempin et al, 2013;Kronenberg et al, 2016;Sachs et al, 2013) and humans with serotonin transporter deficiency (hyperserotonin) reduced the availability of BDNF (Molteni et al, 2010), which enhances NSCs proliferation and neurogenesis (Arsenijevic and Weiss, 1998;Numakawa et al, 2017). Our findings support the negative role of serotonin on BDNF signaling and NSC plasticity.…”
Section: Discussionsupporting
confidence: 73%
“…In stress-related disorders, depletion of serotonin reduces brain BDNF levels [63][64][65]. On the contrary, hyposerotonergic mouse (Tph2−/− or Pet1−/−) showed increased BDNF levels in the hippocampus and prefrontal cortex [60][61][62]66], and humans with SERT deficiency (hyperserotonin) reduced the availability of BDNF [67], which enhances NSCs proliferation and neurogenesis [68,69]. Our findings support the negative role of serotonin on BDNF signaling and NSC plasticity.…”
Section: Discussionsupporting
confidence: 72%
“…Another potential antidepressant mechanism of puerarin (1) and estrogen involves the upregulation of BDNF mRNA expression in the hippocampus. The neurotrophin BDNF has been shown to play an important role not only in the hippocampal synaptic plasticity, the neurobiological basis of learning and memory, but also in emotional performance, such as depression, both of which are mediated by synaptogenesis [36], neurogenesis [37,38], changes in morphologies of cells and dendrites [39], and a modulation of the efficacy of neurotransmitter release [40]. Previous studies showed that patients with depression, as well as various animal models of depression, had reduced BDNF levels in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%